Pengaruh E-Promotion dan E-Word Of Mouth terhadap Keputusan Pembelian melalui Kepuasan Pelanggan sebagai Variabel Intervening pada Pembelian Skincare Facetology Generasi Z - Rona Saniyya; Suci Utami Wikaningtyas (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
Abstract This study aims to examine the effect of e-promotion on customer satisfaction and purchasing decisions, the effect of e-word of mouth on customer satisfaction and purchasing decisions, and the role of customer satisfaction as an intervening variable in the relationship. In addition, this study also examines the effect of e-promotion and e-word of mouth on purchasing decisions through customer satisfaction. The research subjects were Facetology skincare customers. The sample was determined using a non-probability sampling technique with the Hair formula approach, resulting in 100 respondents. Data analysis involved tests of convergent validity, discriminant validity, reliability, R-square, and hypothesis testing. The results showed that e-promotion has a positive effect on customer satisfaction and purchasing decisions. A well-designed digital promotion is able to enhance the customer experience while encouraging them to purchase the product. E-word of mouth also has a positive influence on customer satisfaction and purchase decisions, which means that reviews or recommendations from others can reinforce positive perceptions of the product. Furthermore, customer satisfaction was shown to partially mediate the effect of e-promotion on purchasing decisions, as well as the effect of e-word of mouth on purchasing decisions. This research confirms that e-promotion and e-word of mouth are important marketing strategies that not only increase customer satisfaction, but also contribute to increased purchase decisions, with customer satisfaction as a key factor in this process.